2021
DOI: 10.3390/ijms22052273
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Allergic Rhinitis and Asthma and Laboratory Possibilities for Their Assessment

Abstract: Currently, extracellular vesicles (EVs) have been implicated in the etiopathogenesis of many diseases, including lung disorders, with the possibility of diagnostic and therapeutic applications. The analysis of EV in respiratory tract diseases faces many obstacles, including material collection from airways, standardization of isolation techniques, detection methods, the analysis of their content, etc. This review focuses on the role of extracellular vesicles in the pathogenesis of atopic respiratory diseases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Extracellular vesicles are considered responsible for communication between cells and are frequently used to investigate the pathogenesis of various diseases, including AR. 15 Extracellular vesicles secreted from Gram-negative and Gram-positive bacteria were originally called membrane vesicles (MVs) and outer membrane vesicles (OMVs). Microorganism-associated molecular patterns (MAMPs) such as nucleic acids, peptidoglycan, lipopolysaccharide (LPS), and toxins are present in MVs or OMVs.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular vesicles are considered responsible for communication between cells and are frequently used to investigate the pathogenesis of various diseases, including AR. 15 Extracellular vesicles secreted from Gram-negative and Gram-positive bacteria were originally called membrane vesicles (MVs) and outer membrane vesicles (OMVs). Microorganism-associated molecular patterns (MAMPs) such as nucleic acids, peptidoglycan, lipopolysaccharide (LPS), and toxins are present in MVs or OMVs.…”
Section: Introductionmentioning
confidence: 99%
“…As far as the indirect presentation is concerned, antigen or antigen/MHC complex transfer is also engaged, as well as cross-priming and cross-dressing presentation pathways. These topics have been extensively covered already in excellent publications (138)(139)(140)(141)(142)(143)(144). Hence, since the focus of this review is the EVs secreted by nonimmune cells which are often overlooked but also extensively participate in immune responses, their contribution will be presented next.…”
Section: Immune Cell-derived Evs In Immunitymentioning
confidence: 99%
“…Rapidly accumulating evidence from in vitro , in vivo , and human studies has demonstrated that EVs have a potential role in asthma diagnostic options ( 9 , 10 ). Asthma is a major chronic inflammatory lung disease affecting the quality of life of people of all ages worldwide, characterized by reversible airway obstruction causing dyspnea and cough ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%